(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
Artificial intelligence is presently yielding a lot of benefits to the world and every facet of human endeavors and school administration is no exception. The application of Artificial Intelligence (AI) in effective school Administration has shown a lot of potentials to improve accuracy and timeliness of educational activities and practices. For example, AI helps to create and update content more efficiently, ensuring that the learning materials are up to date and relevant to achieving educational goals. This helps students to stay informed about the latest developments of their chosen fields of study and prepares them for future endeavors and challenges. Hence effective school administration can thus be enhanced through the application of artificial intelligence which helps in the achievement of educational goals. It is on this background, this paper examined Artificial Intelligence in the effective administration of Nigerian schools. The paper therefore explores clarifications of concepts, application of AI in school administration, the implications of AI as well as the challenges of AI in effective administration of schools; as it proffers possible solutions to the observed challenges.